What's your story - Campbell, Caroline (Nelson Melbourne, 2017)
"What's Your Story?" is a children's book that encourages young readers to express their own creativity and share their personal narratives. Through engaging illustrations and prompts, the book invites kids to think about their experiences, dreams, and adventures. It emphasizes the importance of storytelling and self-expression, inspiring children to explore their imaginations and understand the value of their unique perspectives. The interactive nature of the book makes it a wonderful tool for fostering creativity and communication skills in young readers.